2020
DOI: 10.3748/wjg.v26.i38.5836
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous motion of liver correlates to the severity of portal hypertension

Abstract: BACKGROUND Degree of portal hypertension (PH) is the most important prognostic factor for the decompensation of liver cirrhosis and death, therefore adequate care for patients with liver cirrhosis requires timely detection and evaluation of the presence of clinically significant PH (CSPH) and severe PH (SPH). As the most accurate method for the assessment of PH is an invasive direct measurement of hepatic venous pressure gradient (HVPG), the search for non-invasive methods to diagnose these condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In patients with severe cirrhosis, most liver cells are deformed, and hepatic lobular fibers are damaged and divided, leading to blood flow disorder in the liver[ 13 ]. A relevant diagnostic study showed that portal venous blood flow and speed are reduced after liver damage, but the impact on the HAP is small[ 14 ]. Therefore, a reduction in portal venous blood flow will further increase the velocity of HAP blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe cirrhosis, most liver cells are deformed, and hepatic lobular fibers are damaged and divided, leading to blood flow disorder in the liver[ 13 ]. A relevant diagnostic study showed that portal venous blood flow and speed are reduced after liver damage, but the impact on the HAP is small[ 14 ]. Therefore, a reduction in portal venous blood flow will further increase the velocity of HAP blood flow.…”
Section: Discussionmentioning
confidence: 99%